Bacterial pathogenesis and interleukin-17: interconnecting mechanisms of immune regulation, host genetics, and microbial virulence that influence severity of infection. (4th July 2018) - Chamoun, Michelle N.; Blumenthal, Antje; Sullivan, Matthew J.; Schembri, Mark A.; Ulett, Glen C.
Abstract: Interleukin-17 (IL-17) is a pro-inflammatory cytokine involved in the control of many different disorders, including autoimmune, oncogenic, and diverse infectious diseases. In the context of infectious diseases, IL-17 protects the host against various classes of microorganisms but, intriguingly, can also exacerbate the severity of some infections. The regulation of IL-17 expression stems, in part, from the activity of Interleukin-23 (IL-23), which drives the maturation of different classes of IL-17-producing cells that can alter the course of infection. In this review, we analyze IL-17/IL-23 signalling in bacterial infection, and examine the interconnecting mechanisms that link immune regulation, host genetics, and microbial virulence in the context of bacterial pathogenesis. We consider the roles of IL-17 in both acute and chronic bacterial infections, with a focus on mouse models of human bacterial disease that involve infection of mucosal surfaces in the lungs, urogenital, and gastrointestinal tracts. Polymorphisms in IL-17-encoding genes in humans, which have been associated with heightened host susceptibility to some bacterial pathogens, are discussed. Finally, we examine the implications of IL-17 biology in infectious diseases for the development of novel therapeutic strategies targeted at preventing bacterial infection.